The mutational landscape of spinal chordomas and their sensitive detection using circulating tumor DNA. Issue 1 (8th December 2020) - Mattox, Austin K; Yang, Beibei; Douville, Christopher; Lo, Sheng-fu; Sciubba, Daniel; Wolinsky, Jean Paul; Gokaslan, Ziya L; Robison, Jamie; Blair, Cherie; Jiao, Yuchen; Bettegowda, Chetan
Abstract: Background: Chordomas are the most common primary spinal column malignancy in the United States. The aim of this study was to determine whether chordomas may be detected by evaluating mutations in circulating tumor DNA (ctDNA). Methods: Thirty-two patients with a biopsy-confirmed diagnosis of chordoma had blood drawn pre-operatively and/or at follow-up appointments. Mutations in the primary tumor were identified by whole exome sequencing and liquid biopsy by ddPCR and/or RACE-Seq was used to detect one or more of these mutations in plasma ctDNA at concurrent or later time points. Results: At the time of initial blood draw, 87.1% of patients were ctDNA positive ( P < .001). Follow-up blood draws in twenty of the patients suggest that ctDNA levels may reflect the clinical status of the disease. Patients with positive ctDNA levels were more likely to have greater mutant allele frequencies in their primary tumors ( P = .004) and undergo radiotherapy ( P = .02), and the presence of ctDNA may correlate with response to systemic chemotherapy and/or disease recurrence. Conclusions: Detection of ctDNA mutations may allow for the detection and monitoring of disease progression for chordomas.